THE CENTRAL ROLE OF WORK–LIFE BALANCE AND CAREER DEVELOPMENT ON WORK MOTIVATION: AN EMPIRICAL STUDY IN INDONESIAN LOCAL GOVERNMENT AGENCY - Rachmat Hamid; Bambang Supriadi; Harianto Respati; Feriska Andriani (Adisam Publisher, 2025)
This study investigates the direct and indirect influence of Work–Life Balance (WLB) and Career Development (CD) on Work Motivation (WM) among employees in the Indonesian public sector, specifically at the Regional Revenue Agency (BAPENDA) of Malang Regency. The research aims to clarify the mixed empirical findings regarding the determinants of public-sector motivation and to provide practical implications for Human Resource Management (HRM) policies. A quantitative explanatory research design was employed, using a survey-based approach with a saturated sample of 192 BAPENDA Malang Regency employees (54% female, 74% with undergraduate degrees). Data were collected using a structured questionnaire, and the hypotheses were tested using Structural Equation Modeling with Partial Least Squares (PLS-SEM). Descriptive analysis revealed a highly positive organizational climate, with all three variables (WLB, CD, and WM) rated as